Effectiveness of Brogandi (Broccoli and Gotu Kola) on Cognitive Function among Elderly - Fitriana, Lisna Anisa; Darmawati, Irma; Putri, Suci Tuty; Andriyani, Septian; Rustiani, Erni; Hazar, Fatih (Universitas Pendidikan Indonesia, 2024)
Introduction: Broccoli and Gotu Kola (Brogandi) are known to improve cognitive function, but the combination of the two to improve cognitive function is still limited. Objective: This study aimed to analyze the effectiveness of Brogandi in improving cognitive function in healthy elderly, mild dementia and moderate dementia. Methods: This research used a pre and post test design on 38 elderly people at Griya Lansia Garut. Cognitive function examination uses the MMSE (Mini Mental State Examination) questionnaire. The dose of brogandi given is 2x500 mg/day for 14 weeks. Results: Brogandi can improve cognitive function in elderly with mild dementia (p=0.001). Conclusion: Giving Brogandi at a dose of 2x500mg/day for 14 weeks is effective in improving cognitive function in elderly with mild dementia. Meanwhile, in elderly people with moderate dementia, further research needs to be done in the form of increasing the dose and taking a longer administration time.